Business Climate Survey 2010: Mengukur Peringkat Daya Saing Daerah Kalimantan Barat - Memet Agustiar (Jurnal Manajemen dan Usahawan Indonesia, 2022)
West Kalimantan (Kalbar) need a bigger leap to be more advanced, so that regional policy is needed that is able to encourage the competitiveness of West Kalimantan. One initial step is to create a conducive business climate. This study aims to measure the competitiveness of the region of West Kalimantan, especially on competitiveness ranking counties and cities and their performancce on each sub-index, and then analyze the relationship between the total index of the sub-index and between the sub-indexes. Research conducted on 798 respondents fro the company and 42 respondents representing the officials. Data analysis was done by creating composite index of competitiveness that are designed based on the approach that had been done by GIZ to the same survey in Central Java and in Vietnam. This survey bring into 14 districs and cities in West Kalimantan. There are six sub-indices used in this study, i.e.: (1) Economic Performance, (2) Investment Performance, (3) Government Performance, (4) Business Dynamics, (5) Business Environment Perceptions, and (6) Infrastructure. There are two sub-indices that were given higher score than the other, namely the Investment Performance and the Government Performance. The result of this survey placed Kabupaten Singkawang as the first rank in the overall index. The leader in each sub-indices vary in each region. The competitiveness of the West Kalimantan province is moving from the lowest value (3.75) and highest (5.78), with a median of 4.89. This shows the power of West Kalimantan's competitiveness are still below average. For policy considerations, the government and other development actors should seek to continue boosting regional competitiveness through improving the quality of public services and strengthening local infrastructures.